(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMARIO: 1. Introducción - 2. Planteamiento del problema y antecedentes en Europa - 3. El velo integral en la legislación italiana - 4. La sentencia del Consiglio di Stato italiano núm. 3076, de 19 de junio de 2008 - 5. La Delibera 4553, de 10 de diciembre de 2015, de la Giunta Regionale de Lombardía - 6. La sentencia del Tribunal de Milán de 20 de abril de 2017 – 7. La valoración de la Corte di Appello di Milano: la sentencia de 28 de octubre de 2019 - 8. El velo integral en el ordenamiento jurídico español – 9. La Ordenanza Municipal de Civismo y Convivencia de Lleida y su interpretación por el Tribunal Superior de Justicia de Cataluña - 10. La anulación de la Ordenanza Municipal de Civismo y Convivencia de Lleida por el Tribunal Supremo: la sentencia núm. 693 de 2013, de 14 de febrero - 11. La Ordenanza de Civismo de la ciudad de Reus y los autos del Tribunal Superior de Justicia de Cataluña - 12. Síntesis conclusiva: estudio comparativo de las realidades lombarda y catalana. The ban on the integral veil in Italy and Spain: the Lombard and Catalan cases ABSTRACT: In recent years we have been able to appreciate how phenomena such as immigration and globalization have transformed the religious decoration of European countries. Italy and Spain do not represent any exception, because in the streets of their towns and villages there is a growing religious diversity that every day does not stop increasing. That this means people who have arrived to Italy and Spain searching of better prospects for the future but without forgetting their customs, traditions and religion. The problems arise when in use of religious freedom, this people try that the host society admits or tolerates certain religious practices, foreign to the European Judeo-Christian tradition, which could collide with the European legal order. One of those controversial practices has to do with religious symbology, specifically, with the integral veil that Islamic women carry, mainly because of the security problems. By this reason, this article tries to describe the legal situation of the integral veil, analyzing and comparing the ways in which have been regulated in Italy (Lombardy) and Spain (some Catalonian municipalities like Lleida or Reus). The jurisprudential solutions emanating from the courts of both countries are also studied.